A new hierarchical architecture and protocol for key distribution in the context of IoT-based smart cities. (June 2022) - AbuAlghanam, Orieb; Qatawneh, Mohammad; Almobaideen, Wesam; Saadeh, Maha
Abstract: The Internet of Things (IoT) is a system of objects such as traditional computers, cameras, sensors and other things that are interconnected via a network to gather, process, and exchange context relevant data. Security is considered as one of the most important challenges facing IoT. Key distribution techniques are at the core of security provision and are critical components of any system in order to establish a secure connection between any two objects. In this paper a new Hierarchical Key Distribution (HKD) architecture and a set of Hierarchical Hybrid Key Distribution (H2KD) protocols are presented for IoT environment to support the provision of smart cities applications. The applicability of this protocols has been studied over HKD architecture and simulated using AVISPA tool and using Burrows–Abadi–Needham (BAN) logic. The targeted features of designing the architecture and the protocols are supporting mobility, scalability, heterogeneity and supporting constrained nodes' limited capabilities. The performance of H2KD set of protocols has been evaluated based on a quantitative measure of several performance metrics including the memory storage, the computation cost for the constraint nodes, the number of messages exchanged and needed to establish a new session key for a mobile node. Scalability and resilience of the proposed protocols have been also measured. Simulation results show that H2KD protocols are safe against various attacks. Moreover, the analysis results show that the H2KD reduces communication, computation, and the storage costs for constraint nodes by 51.5% compared with related protocols. Additionally, H2KD has been found to provide more scalability and resilience than rival protocols.